Combating Escherichia coli O157:H7 with Functionalized Chickpea‐Derived Antimicrobial Peptides. Issue 6 (23rd December 2022) - He, Qiao; Yang, Zhehao; Zou, Zhipeng; Qian, Mengyan; Wang, Xiaolei; Zhang, Xinhui; Yin, Zhongping; Wang, Jinhai; Ye, Xingqian; Liu, Donghong; Guo, Mingming
Abstract: The rapid dissemination of antibiotic resistance accelerates the desire for new antibacterial agents. Here, a class of antimicrobial peptides (AMPs) is designed by modifying the structural parameters of a natural chickpea‐derived AMP–Leg2, termed "functionalized chickpea‐derived Leg2 antimicrobial peptides" (FCLAPs). Among the FCLAPs, KTA and KTR show superior antibacterial efficacy against the foodborne pathogen Escherichia coli ( E. coli ) O157:H7 (with MICs in the range of 2.5–4.7 µmol L −1 ) and demonstrate satisfactory feasibility in alleviating E. coli O157:H7‐induced intestinal infection. Additionally, the low cytotoxicity along with insusceptibility to antimicrobial resistance increases the potential of FCLAPs as appealing antimicrobials. Combining the multi‐omics profiling andpeptide‐membrane interaction assays, a unique dual‐targeting mode of action is characterized. To specify the antibacterial mechanism, microscopical observations, membrane‐related physicochemical properties studies, and mass spectrometry assays are further performed. Data indicate that KTA and KTR induce membrane damage by initially targeting the lipopolysaccharide (LPS), thus promoting the peptides to traverse the outer membrane. Subsequently, the peptides intercalate into the peptidoglycan (PGN) layer, blocking its synthesis, and causing a collapse of membrane structure. These findings altogether imply the great potential of KTA and KTR as promising antibacterial candidates in combating the growing threat of E. coli O157:H7. Abstract : Functionalized chickpea‐derived Leg2 antimicrobial peptides (FCLAPs) show superior antibacterial activity, and they combat Escherichia coli O157:H7 through a dual‐targeting mechanism. First, FCLAPs induce membrane damage by initially targeting the lipopolysaccharide, thus promoting the peptides to traverse the outer membrane. Subsequently, the peptides intercalate into the peptidoglycan layer, blocking its synthesis, and causing a collapse of membrane structure.